Thavirat, UMPSA-BJTU Dual Degree Programme pioneer student, excited to become Electrification System Engineer at MRL - Mimi Rabita, Abdul Wahit (UMPSA, 2025)
PEKAN, 14 February 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) student, Thavirat Supkhasin a/l Aran, 26, a pioneer graduate of the UMPSA-Beijing Jiaotong University (BJTU) Dual Degree Programme, is excited to begin his career as an Electrification System Engineer at Malaysia Rail Link Sdn. Bhd. (MRL), Dungun, Terengganu, starting on 5 March. This Kelantane now holds a degree in Electrical Engineering in Automation from BJTU.